FACTORS TO INCREASE SALES WEDDING PACKAGE SELLING AT FOUR SEASONS RESORT BALI AT JIMBARAN BAY - Ni Putu Suryaningsih; I Ketut Sutama; A A Putu Swabawa (Journal of Applied Sciences in Travel and Hospitality, 2018)
The research was conducted at Four Seasons Resort Bali at Jimbaran Bay which aims to find out the factors to increase the sales of wedding packages at Four Seasons Resort Bali at Jimbaran Bay. The problem statement in this research is what factors become the strength, weakness, opportunity and threat for Four Seasons Resort Bali at Jimbaran Bay to increase the sale of wedding tourism package? This research is a qualitative descriptive research that collects primary data by observation, interview, documentation and triangulation. Sampling method used is purposive sampling method. Determination of internal factors of company using IFAS matrix, while determining factor external company using EFAS matrix. Based on the method used, the company's strength are customized wedding package, wedding package price and ocean view wedding package, while the weakness of the company are the capacity of small wedding venue, no chapel in wedding venue and not located on cliff side. Opportunities that are owned by the company are the popularity of the famous brand, the conducive stability of the security of Bali and the changes of worldwide community style, while the threat faced by the company are the capacity of a larger competitor wedding venue, the promotion offered by competitors and the number of wedding chapel / venue in South Kuta area